9514 1404 393
Answer:
x = 3.6
Step-by-step explanation:
The angle bisector divides the triangle proportionally.
The base segment to the right of the bisector is 6-x, so we can write the proportion ...
x/6 = (6-x)/4
Multiplying by 12, we get ...
2x = 3(6 -x)
5x = 18 . . . . . add 3x
x = 18/5 . . . . divide by 5
x = 3.6
_____
<em>Alternate solution</em>
Since the base of the triangle is given as a left-part and a sum-of-both-parts, we can write the proportion the same way:
left-part / sum-of-both-parts = x/6 = 6/(6+4)
Then the solution is x = 6(6/10) = 36/10 = 3.6.
Doing it this way avoids having x on both sides of the equation, so makes solving the equation be "one step."
Answer:
Answer 30^{2}
Step-by-step explanation:
24^{2} + 18^ {2} = c^{2}
576 + 324 = c^{2}
\sqrt{900} c^{2} = 30
hope this helps!
Answer: 34/9
Step-by-step explanation:
5 2/3 / 3/2
= 17/3 / 3/2
=17/3 x 2/3 [reciprocal]
=34/9
Hope it helped u,
pls mark as the brainliest
^_^
Answer:
In graph
Step-by-step explanation:
First put it in Slope -Intercept form.
then graph the y- intercept first.
After that it's rise over run so think 1/1
up 1 over one.